Maternal lifestyle and nutritional status in relation to pregnancy and infant health outcomes in Western China: Protocol for a prospective cohort study - Tang, L.; Pan, X.; Lee, A.; Binns, Colin; Yang, C.; Sun, X. (BM J Group, 2017)
No commercial use is permitted unless otherwise expressly granted. Introduction Improving the health and nutrition of women and children is a priority for Western China, where the economy is less developed. Due to the dynamic nature of lifestyle, modern food habits and nutrition, there is a need to update our limited knowledge and understanding of maternal lifestyle and nutritional status and their impact on pregnancy and infant health outcomes. While breast milk is the preferred feeding option, infant formula use is widespread in China. It is thus necessary to examine the effects of formula consumption on growth and morbidity. Methods and analysis This is an ongoing prospective cohort study started in 2015 in Chengdu, Sichuan Province. A sample of 1901 pregnant women at 15-20 weeks of gestation were recruited from four maternal and child health hospitals and are followed prospectively to 12 months post partum. Detailed information on maternal lifestyle and nutritional status, obstetric complications, pregnancy outcomes, infant feeding practices, illnesses of the mother and infant and growth trajectory is collected through personal interviews, anthropometric measures and medical records and local health management system records retrieval. Multilevel mixed regression models, adjusted for clustering, will be applied to investigate the association between various exposure variables of interest and the longitudinal outcomes, taking into account the correlated data structure and the nesting of observations. Kaplan-Meier test and Cox regression analysis will be used to analyse the time-to-event data. Ethics and dissemination Ethical approval has been obtained from the ethics committee of West China School of Public Health, Sichuan University and the Human Research Ethics Committee of Curtin University. Results will be presented at national and international conferences and published in peer-reviewed journals.